PERAN SISTEM INFORMASI MANAJEMEN DI SEKOLAH SMP MUHAMMADIYAH KOTA BANDUNG - Tarmidzi, Inayah; Hidayati, Dian (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study focused on examining the management of learning information systems and its impact on organizational development. The research employed both interview and literature study methods to gather relevant material, data, and information from various sources such as books, journals, and articles pertaining to the subject matter. The findings of the study indicate that computer-based systems, particularly the School Information Management (SIM) system, enable educational institutions to efficiently and effectively carry out learning activities aligned with their organizational objectives. Computer-based management information systems offer numerous advantages, including speedy processing, high accuracy, and other beneficial features that contribute to organizational growth. In conclusion, this research establishes that management information systems play a crucial role in supporting the advancement of learning processes. By leveraging the benefits of these systems, educational institutions can foster development and progress in their learning environments.